2018
DOI: 10.3390/nu10101387
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of a Pulse-Based Diet and the Therapeutic Lifestyle Changes Diet in Combination with Exercise and Health Counselling on the Cardio-Metabolic Risk Profile in Women with Polycystic Ovary Syndrome: A Randomized Controlled Trial

Abstract: We compared the effects of a low-glycemic index pulse-based diet, containing lentils, beans, split peas, and chickpeas, to the Therapeutic Lifestyle Changes (TLC) diet on cardio-metabolic measures in women with polycystic ovary syndrome (PCOS). Ninety-five women (18–35 years) enrolled in a 16-week intervention; 30 women in the pulse-based and 31 in the TLC groups completed the study. Women participated in aerobic exercise training (minimum 5 days/week for 45 min/day) and were counselled (monthly) about PCOS an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
89
0
6

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 82 publications
(105 citation statements)
references
References 111 publications
(140 reference statements)
10
89
0
6
Order By: Relevance
“…of either a therapeutic lifestyle changes diet or a pulse-based diet in women with PCOS, those on the pulse diet had a greater decrease in cardio-metabolic risk factors such as LDL-cholesterol and insulin response to OGTT 60 . As previously reported 25,26 , our PCOS mouse model mimics PCOS associated dyslipidemia, with an increase in serum cholesterol levels.…”
Section: Discussionmentioning
confidence: 96%
“…of either a therapeutic lifestyle changes diet or a pulse-based diet in women with PCOS, those on the pulse diet had a greater decrease in cardio-metabolic risk factors such as LDL-cholesterol and insulin response to OGTT 60 . As previously reported 25,26 , our PCOS mouse model mimics PCOS associated dyslipidemia, with an increase in serum cholesterol levels.…”
Section: Discussionmentioning
confidence: 96%
“…One study reported statistically significant within-group decreases in FBI for both the control and legume interventions (p < 0.01), and a 12-month follow-up also reported a significant within-group reduction in both the intervention and control groups (p < 0.02) [35] (Table 7). One study observed a statistically significant within-group decrease in HOMA-IR for the legume intervention (p < 0.001) [35], and another observed a statistically significant within-group decrease in HbA1c for the legume intervention (p = 0.01) [36]; however, both studies also observed a statistically significant effect in control arms. One study reported a statistically significant between-group effect for 2-h PPG (p = 0.01) in favour of the control [36], and another study reported a statistically significant within-group decrease (p < 0.0001) in both the control and intervention arms [35] (Table S4).…”
Section: Individuals Without Diabetes Mellitusmentioning
confidence: 98%
“…The 12 identified RCTs conducted on individuals without diabetes mellitus reported inconsistent results, albeit no between-group effects observed were statistically significant. Two studies reported a statistically significant within-group decrease in FBG for the legume intervention [29,35]; however, one of these also reported a statistically significant within-group decrease in the control intervention arm [35] (Table 6). One study reported statistically significant within-group decreases in FBI for both the control and legume interventions (p < 0.01), and a 12-month follow-up also reported a significant within-group reduction in both the intervention and control groups (p < 0.02) [35] (Table 7).…”
Section: Individuals Without Diabetes Mellitusmentioning
confidence: 99%
See 1 more Smart Citation
“…In women with PCOS, several one‐, two‐, and three‐component lifestyle programs have been tested (3,11,12). Many LS focused on diet and exercise and included no behavioral modification like the 16‐week intervention of Kazemi and colleagues (13), the 20‐week intervention of Thomson and colleagues (14) ( n = 94), and the 16‐week intervention ( n = 50) of Legro and colleagues (15), which also included weight‐loss medication. Some LS focused on CBT only or included CBT techniques, like the pilot intervention of Cooney and colleagues ( n = 33) that compared 16 individual 30‐minute nutrition/exercise counseling sessions to 8 additional 30‐minute brief CBT sessions (16).…”
Section: Introductionmentioning
confidence: 99%